Many-body enhanced nonlinear conductance resonance in quantum channels - Han, Jong E.; Fischer, Saskia F.; Buchholz, Sven S.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D.; Bird, Jonathan P. (Physical Review B)

Dynamic Nuclear Spin Resonance inn-GaAs - Chen, Y. S.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Physical Review Letters)

Optical Control of Coherent Interactions between Electron Spins in InGaAs Quantum Dots - Spatzek, S.; Greilich, A.; Economou, Sophia E.; Varwig, S.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Physical Review Letters)

Generation and detection of mode-locked spin coherence in (In,Ga)As/GaAs quantum dots by laser pulses of long duration - Spatzek, S.; Varwig, S.; Glazov, M. M.; Yugova, I. A.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Edge-induced magnetoplasmon excitation in a two-dimensional electron gas under quantum Hall conditions - Notthoff, Christian; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel (Physical Review B)

Resonant nuclear spin pumping in (In,Ga)As quantum dots - Cherbunin, R. V.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kuznetsova, M. S.; Petrov, M. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Electrostatically trapping indirect excitons in coupled InxGa1−xAs quantum wells - Schinner, G. J.; Schubert, E.; Stallhofer, M. P.; Kotthaus, J. P.; Schuh, D.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O. (Physical Review B)

Polarization-preserving confocal microscope for optical experiments in a dilution refrigerator with high magnetic field - Sladkov, Maksym; Bakker, M. P.; Chaubal, A. U.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Review of Scientific Instruments)

Mode-filtered electron injection into a waveguide interferometer - Buchholz, Sven S.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D.; Fischer, Saskia F. (Applied Physics Letters)

Optically detected nuclear magnetic resonance in n-GaAs using an on-chip microcoil - Chen, Y. S.; Huang, J.; Reuter, Dirk; Ludwig, A.; Wieck, A. D.; Bacher, G. (Applied Physics Letters)

Transport spectroscopy of non-equilibrium many-particle spin states in self-assembled quantum dots - Marquardt, B.; Geller, M.; Baxevanis, B.; Pfannkuche, D.; Wieck, A. D.; Reuter, Dirk; Lorke, A. (Nature Communications)

Strong temperature destabilization of free exciton recombination in a two-dimensional structures with hole gas - Jadczak, J; Bryja, L; Wójs, A; Bartsch, G; Yakovlev, D R; Bayer, M; Plochocka, P; Potemski, M; Reuter, Dirk; Wieck, A (Journal of Physics: Conference Series)

Phonon-assisted exciton spin relaxation in (In,Ga)As/GaAs quantum dots - Kurtze, H.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (physica status solidi (c))

Structural, optical, and magnetic properties of Ho-implanted GaN thin films - Lo, F-Y; Guo, J-Y; Ney, V; Ney, A; Chern, M-Y; Melnikov, A; Pezzagna, S; Reuter, Dirk; Wieck, A D; Massies, J (Journal of Physics: Conference Series)

Towards the quantized magnetic confinement in quantum wires - Cerchez, M.; Tarasov, A.; Hugger, S.; Xu, Hengyi; Heinzel, T.; Zozoulenko, I. V.; Gasser-Szerer, U.; Reuter, Dirk; Wieck, A. D.; Ihm, Jisoon; Cheong, Hyeonsik

All-electrical transport spectroscopy of non-equilibrium many-particle states in self-assembled quantum dots - Marquardt, Bastian; Geller, Martin; Baxevanis, Benjamin; Pfannkuche, Daniela; Wieck, Andreas D.; Reuter, Dirk; Lorke, Axel; Ihm, Jisoon; Cheong, Hyeonsik

Electromagnetically induced transparency in low-doped n-GaAs - van der Wal, C. H.; Sladkov, M.; Chaubal, A. U.; Bakker, M. P.; Onur, A. R.; Reuter, Dirk; Wieck, A. D.; Ihm, Jisoon; Cheong, Hyeonsik

Manipulation of nuclear spin dynamics in n-GaAs using an on-chip microcoil - Chen, Y. S.; Huang, J.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Journal of Applied Physics)

‘It’s Almost Like Taking the Sales out of Selling’: Conceptualizing Value-Based Selling in Business Markets - Terho, H; Haas, A; Eggert, A; Ulaga, W (2011 AMA Summer Marketing Educators' Proceedings)

Service orientation of manufacturing companies: A necessary or sufficient condition for firm profitability? - Eggert, A; Münkhoff, E; Thiesbrummel, C (Proceedings of the 40th European Marketing Academy (EMAC) Conference)

Embracing the complexity of recovery management in business-to-business relationships - Doescher, K; Hogreve, J; Eggert, A (Proceedings of the 40th European Marketing Academy (EMAC) Conference)

All or Nothing at All – Referral Reward Programs, Customer Retention and Reward Size - Garnefeld, I; Helm, S; Eggert, A; Tax, S (Proceedings of the 40th European Marketing Academy (EMAC) Conference)

Time extension of sales promotions – How do customers react? - Münkhoff, E; Garnefeld, I; Bruns, A (Proceedings of the 40th European Marketing Academy (EMAC) Conference)

Assessing the long-term effect of industrial services on firm profitability: The moderating impact of product innovations - Eggert, A; Hogreve, J; Ulaga, W; Münkhoff, E (2011 AMA Winter Marketing Educators' Proceedings)

Identifying Valence as a Contingency Variable for the Primacy-Recency-Controversy - Eggert, A; Garnefeld, I; Steinhoff, L (2011 AMA Winter Marketing Educators' Proceedings)

Can Retailers Improve Loyalty by Empowering Consumers? - Hunter, G; Garnefeld, I; Steinhoff, L (2011 AMA Winter Marketing Educators' Conference Proceedings)

Content, connectivity, and cloud: ingredients for the network of the future - Ahlgren, Bengt; A. Aranda-Gutierrez, Pedro; Chemouil, Prosper; Oueslati, Sara; M. Correia, L; Karl, Holger; Söllner, Michael; Welin, Annikki (IEEE Communications Magazine)

Research challenges towards the Future Internet - Conti, Marco; Chong, Song; Fdida, Serge; Jia, Weijia; Karl, Holger; Lin, Ying{-}Dar; M{\, Petri; Maier, Martin; Molva, Refik; Uhlig, Steve; Zukerman, Moshe (Computer Communications)

MDHT: A hierarchical name resolution service for information-centric networks - D'Ambrosio, Matteo; Dannewitz, Christian; Karl, Holger; Vercellone, Vinicio (2011 ACM SIGCOMM Workshop on Information-Centric Networking, ICN 2011, Toronto, ON, Canada, August 19, 2011)

Multihop Performance of Cooperative Preamble Sampling MAC(CPS-MAC) in Wireless Sensor Networks - Azeem M. Khan, Rana; Karl, Holger (Ad-hoc, Mobile, and Wireless Networks - 10th International Conference, ADHOC-NOW 2011, Paderborn, Germany, July 18-20, 2011. Proceedings)

Reducing power consumption of mobile access networks with cooperation - Herlich, Matthias; Karl, Holger (2nd International Conference on Energy-Efficient Computing and Networking 2011, e-Energy '11, New York, NY, USA - May 31 - June 01, 2011)

A Game-Theoretical Approach to the Benefits of Cloud Computing - Künsemöller, Jörn; Karl, Holger (Economics of Grids, Clouds, Systems, and Services - 8th International Workshop, GECON 2011, Paphos, Cyprus, December 5, 2011, Revised Selected Papers)

Coding Opportunities from Similar Data in Wireless Cooperation Diversity Systems - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (IEEE 8th International Conference on Mobile Adhoc and Sensor Systems, MASS 2011, Valencia, Spain, October 17-22, 2011)

Designing optical metro and access networks for future cooperative cellular systems - Biermann, Thorsten; Scalia, Luca; Karl, Holger (Proceedings of the 14th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2011, Miami, Florida, USA, October 31 - November 4, 2011)

The Trade-Off between Power Consumption and Latency in Computer Networks - Herlich, Matthias; Karl, Holger (NETWORKING 2011 Workshops - International IFIP TC 6 Workshops, PE-CRN, NC-Pro, WCNS, and SUNSET 2011, Held at NETWORKING 2011, Valencia, Spain, May 13, 2011, Revised Selected Papers)

Improving CoMP cluster feasibility by dynamic serving base station reassignment - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Karl, Holger; Kellerer, Wolfgang (IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2011, Toronto, ON, Canada, September 11-14, 2011)

Backhaul Design and Controller Placement for Cooperative Mobile Access Networks - Biermann, Thorsten; Scalia, Luca; Widmer, J.; Karl, Holger (Proceedings of the 73rd IEEE Vehicular Technology Conference, VTC Spring 2011, 15-18 May 2011, Budapest, Hungary)

Backhaul network pre-clustering in cooperative cellular mobile access networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Karl, Holger; Kellerer, Wolfgang (12th IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks, WOWMOM 2011, Lucca, Italy, 20-24 June, 2011)

Kompatibilitätsanalyse bei Evolution framework-basierter Anwendungen - Christ, Fabian; Bals, Jan-Christopher (Proceedings of the 3rd Design for Future Workshop held at the Software Engineering 2011 Conference (SE2011), Karlsruhe (Germany))

A Reference Architecture for Semantic Content Management Systems - Christ, Fabian; Nagel, Benjamin (Proceeding of the Enterprise Modelling and Information Systems Architectures Workshop 2011 (EMISA'11), Hamburg (Germany))

Situational Software Engineering: Ein Rahmenwerk für eine situationsgerechte Auswahl von Entwicklungsmethoden und Vorgehensmodellen - Engels, Gregor; Kremer, Marion (Proceedings der41. Jahrestagung der Gesellschaft für Informatik - Informatik 2011;)

Services aus der Cloud = Fahren im Nebel? Wie minimiere ich die Risiken und erreiche hohe Qualität? - Engels, Gregor (Proceedings der 41. Jahrestagung der Gesellschaft für Informatik - Informatik 2011)
Der Kostendruck einerseits und die Verfügbarkeit des Internets andererseits führen dazu, dass Softwaresysteme auf Services aus der Cloud zurückgreifen (müssen bzw. können). Dies gilt für alle Anwendungsbereiche und somit insbesondere auch für die Software im Auto. Aber wie sorge ich dafür, dass die Services aus der Cloud zu meinem Softwaresystem passen und die Anforderungen erfüllen? Der Vortrag diskutiert aktuelle Ansätze der konstruktiven und analytischen Qualitätssicherung, um durch Maßnahmen sowohl zur Entwicklungs- als auch Laufzeit eine hohe Qualität beim Einsatz von Services aus der Cloud zu erzielen. Insbesondere wird über aktuelle Arbeiten im neuen DFG Sonderforschungsbereich 901 "On-the-Fly Computing" berichtet.

Precise Mappings between Business Process Models in Versioning Scenarios - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor (Proceedings of the IEEE 8th International Conference on Services Computing (SCC'11))

Selektionswerkzeug zur Auswahl projektspezifischer Vorgehensstrategien - Heinemann, Marianne; Palme, Markus; Rothmann, Andreas; Salger, Frank; Schönke, Jürgen; Engels, Gregor (Software Engineering 2011)

Pattern-Based Modeling and Formalizing of Business Process Quality Constraints - Khaluf, Lial; Gerth, Christian; Engels, Gregor (Proceedings of the 23rd International Conference on Advanced Information System Engineering (CAiSE'11))
The quality of business processes can be checked by verifying their compliance with specific quality constraints. These constraints represent a set of required temporal and logical relationships between different steps of business processes. Quality constraints are usually formulated as informal texts, which makes them difficult to be verified, when business processes become complex. One way to solve this problem is by automating the verification of quality constraints on business processes by applying model checking. To apply model checking, both business processes and quality constraints have to be formalized. In this paper, we define a new visual language for modeling quality constraints and we provide a pattern-based translation for quality constraint models into Computation Tree Logic formulas.

Authentifizierte Eingaben auf Multitouch-Tischen - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

Adapt Cases: Extending Use Cases for Adaptive Systems - Luckey, Markus; Nagel, Benjamin; Gerth, Christian; Engels, Gregor (Proceeding of the 6th international symposium on Software engineering for adaptive and self-managing systems)

QUAASY - QUality Assurance of Adaptive SYstems - Luckey, Markus; Gerth, Christian; Soltenborn, Christian; Engels, Gregor (Proceedings of the 8th International Conference on Autonomic Computing (ICAC'11))

Extending DMM Behavior Specifications for Visual Execution and Debugging - Bandener, Nils; Soltenborn, Christian; Engels, Gregor (Proceedings of the 3rd International Conference on Software Language Engineering (SLE 2010))

Testen von Software-Produktlinien - Brüseke, Frank; Christ, Fabian; Sauer, Stefan; Wübbeke, Andreas

Automated Negotiations Under Uncertain Preferences - Lang, Fabian; Schryen, Guido; Fink, Andreas (Proceedings of the 2011 International Conference on Information Systems (ICIS 2011))

Reducing Datacenter Energy Usage through Efficient Job Allocation - Bodenstein, Christian; Schryen, Guido; Neumann, Dirk (Proceedings of the 19th European Conference on Information Systems (ECIS 2011))

Management und Marketing ferngesteuerter Dienstleistungen: Konzeptionelle Verortung, betriebswirtschaftliche Herausforderungen und künftige Forschungsaufgaben. - Wünderlich, Nancy; Schumann, Jan H; Wangenheim, Florian v; Holzmüller, Hartmut H (Zeitschrift für Betriebswirtschaft)
Die Möglichkeiten der Erbringung von Dienstleistungen haben sich durch die Entwicklungen der Informations- und Kommunikationstechnologien stark erweitert. Unter Zuhilfenahme moderner Formen der Datenfernübertragung kann eine breite Palette von Dienstleistungen technologisch vermittelt über große Entfernungen hinweg erbracht werden. Diesen als ferngesteuerte Dienstleistungen bezeichneten Angeboten kommt in der Praxis eine immer größere Bedeutung zu. In der betriebswirtschaftlichen Literatur wurde ihnen bisher jedoch wenig Beachtung geschenkt. In diesem Überblicksartikel erfolgt daher eine erste Auseinandersetzung mit betriebswirtschaftlich relevanten Aspekten ferngesteuerter Dienstleistungen. Ausgehend von einer begrifflichen Abgrenzung und Konzeptualisierung dieses neuen Dienstleistungstypus im Abgleich mit bestehenden Systematisierungsansätzen werden die spezifischen Herausforderungen des Management und Marketing von ferngesteuerten Dienstleistungen reflektiert und sowie künftige Forschungsaufgaben abgeleitet.
Keywords: Technologieintensive Dienstleistungen; remote services; Dienstleistungstechnologien

The Impact of Delegating Decision Making to IT on the Sunk Cost Effect - Herrmann, Philipp; Kundisch, Dennis; Rahman, M. (12th Workshop on Information Systems and Economics (WISE))

Ausgewogener Prozess - Wehner, M C; Kabst, Rüdiger; Kötter, P M

Bewerber wertschätzen - Wehner, M C; Kabst, Rüdiger

Eine vergessene Disziplin - Kabst, Rüdiger; Meifert, M; Wehner, M C

Editorial: Mitarbeiter führen: Ein alter Hut? - Kabst, Rüdiger

SME International Mode Choice Over Time: Forging a Link Between the Uppsala Model and Transaction Cost Economics - Maekelburger, B; Schwens, C; Kabst, Rüdiger (Entrepreneurship in the Global Firm (Progress In International Business Research, Volume 6))

Beschäftigungsformen und OCB: der moderierende Einfluss von Arbeitszufriedenheit - Isidor, R; Steinmetz, Holger; Kabst, Rüdiger

Der Einfluss bio-demographischer und aufgabenorientierter Diversität auf die Leistung von Teams: Eine Metaanalyse. - Schneid, M; Isidor, R; Steinmetz, Holger; Kabst, Rüdiger; Weber, H

Age diversity and team outcomes: A quantitative review. - Schneid, M; Isidor, R; Steinmetz, Holger; Kabst, Rüdiger; Diehl, A

Exploiting New Interaction Techniques for Disaster Control Management Using Multitouch-, Tangible- and Pen-Based-Interaction - Nebe, Karsten; Klompmaker, Florian; Jung, Helge; Fischer, Holger Gerhard (Human-Computer Interaction. Interaction Techniques and Environments.)

Advertisement-Image congruity in the recruitment context - Baum, M; Schaefer, M; Kabst, Rüdiger

Applicant reactions to outsourcing of the recruitment: Does corporate image compensate for negative applicant reactions? - Wehner, M C; Giardini, A; Kabst, Rüdiger

Der Personalverantwortliche als „Strategic Architect“: Persönliche Einstellung oder subjektive Norm? - Wehner, M C; Kabst, Rüdiger; Meifert, M; Cunz, L M

Die komplementäre Wirkung von unternehmerischer Orientierung, Marktorientierung und Lernorientierung auf den Unternehmenserfolg junger Technologieunternehmen - Deutscher, F; Schwens, C; Zapkau, F B; Kabst, Rüdiger

Multitouch-, Be-Greifbare- und Stiftbasierte-Interaktion in der Einsatzlageplanung - Nebe, Karsten; Fischer, Holger Gerhard; Klompmaker, Florian; Jung, Helge (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

Authentifizierte Eingaben auf Multitouch-Tischen - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

A Holistic Model for Integrating Usability Engineering and Software Engineering Enriched with Marketing Activities - Fischer, Holger Gerhard; Nebe, Karsten; Klompmaker, Florian (Human Centered Design)

Der Qualitätsstandard für Usability Engineering der German UPA – Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Bogner, Christian; Geis, Thomas; Polkehn, Knut; Zimmermann, Dirk (Jahresband Usability Professionals)

Disentangling the Effect of Prior Entrepreneurial Exposure on Entrepreneurial Intention – An empirical Analysis based on the Theory of Planned Behavior - Zapkau, F B; Schwens, C; Steinmetz, Holger; Kabst, Rüdiger

The influence of entrepreneurial traits on the strategic orientation and new product success in high-technology firms - Maekelburger, B; Zapkau, F B; Kabst, Rüdiger

Methodology of the Cranet Survey - International Executive Report 2011, Cranfield - Kabst, Rüdiger; Wehner, M C

Innovative Lehrkräfte- und Schulentwicklung. Das Wirtschaftspädagogische Graduiertenkolleg der Universität Paderborn - Sloane, Peter F. E.; Kremer, H.-Hugo; Krakau, U. (Wirtschaft und Erziehung)

Vorteile der Paketbildung in Verhandlungen: Ein prozeduraler Zugang zu Superadditivität - Diehl, Matthias

Bidirectionally Coupled Network and Road Traffic Simulation for Improved IVC Analysis - Sommer, Christoph; German, Reinhard; Dressler, Falko (IEEE Transactions on Mobile Computing)
Recently, many efforts have been made to develop more efficient Inter-Vehicle Communication (IVC) protocols for on-demand route planning according to observed traffic congestion or incidents, as well as for safety applications. Because practical experiments are often not feasible, simulation of network protocol behavior in Vehicular Ad Hoc Network (VANET) scenarios is strongly demanded for evaluating the applicability of developed network protocols. In this work, we discuss the need for bidirectional coupling of network simulation and road traffic microsimulation for evaluating IVC protocols. As the selection of a mobility model influences the outcome of simulations to a great deal, the use of a representative model is necessary for producing meaningful evaluation results. Based on these observations, we developed the hybrid simulation framework Veins (Vehicles in Network Simulation), composed of the network simulator OMNeT++ and the road traffic simulator SUMO. In a proof-of-concept study, we demonstrate its advantages and the need for bidirectionally coupled simulation based on the evaluation of two protocols for incident warning over VANETs. With our developed methodology, we can advance the state-of-the-art in performance evaluation of IVC and provide means to evaluate developed protocols more accurately.

User-space Scheduling for Heterogeneous System under Linux - Welp, Daniel

Towards Systematic, Comprehensive Trace Generation for Behavioral Pattern Detection through Symbolic Execution - von Detten, Markus (Proceedings of the 10th ACM SIGPLAN/SIGSOFT Workshop on Program Analysis for Software Tools and Engineering (PASTE))
In reverse engineering, dynamic pattern detection is accomplished by collecting execution traces and comparing them to expected behavioral patterns. The traces are collected by manually executing the program in question and therefore represent only part of all relevant program behavior. This can lead to false conclusions about the detected patterns. In this paper, we propose to generate all relevant program traces by using symbolic execution. In order to reduce the created trace data, we allow to limit the trace collection to a user-selectable subset of the statically detected pattern candidates.

Stabilizing consensus with the power of two choices - Doerr, Benjamin; Goldberg, Leslie Ann; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Proceedings of the 23rd ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In the standard consensus problem there are n processes with possibly di®erent input values and the goal is to eventually reach a point at which all processes commit to exactly one of these values. We are studying a slight variant of the consensus problem called the stabilizing consensus problem [2]. In this problem, we do not require that each process commits to a ¯nal value at some point, but that eventually they arrive at a common, stable value without necessarily being aware of that. This should work irrespective of the states in which the processes are starting. Our main result is a simple randomized algorithm called median rule that, with high probability, just needs O(logmlog log n + log n) time and work per process to arrive at an almost stable consensus for any set of m legal values as long as an adversary can corrupt the states of at most p n processes at any time. Without adversarial involvement, just O(log n) time and work is needed for a stable consensus, with high probability. As a by-product, we obtain a simple distributed algorithm for approximating the median of n numbers in time O(logmlog log n + log n) under adversarial presence.

Weblogs zur Unterstützung der Theorie-Praxis-Integration in der Wirtschaftslehrenden-Ausbildung - Jenert, Tobias; Gebhardt, Anja; Käser, Reto (Zeitschrift für E-Learning)
Eine zentrale Herausforderung in der Ausbildung angehender Wirtschaftslehrpersonen stellt die sinnvolle Verknüpfung von Theorie- und Praxiserfahrungen dar. Im Rahmen der Ausbildung angehender Wirtschaftslehrpersonen an der Universität St. Gallen wird eine Lernumgebung gestaltet, die eine Verschränkung von Theorie- und Praxiserfahrungen ermöglichen soll. Die Lernprozesse der Studierenden werden dabei durch didaktisch angeleitete Weblogarbeit unterstützt. Trotz der Lernchancen, die sich aus einer Verknüpfung von theoretischen und praktischen Lernphasen ergeben, schätzen die Studierenden den Nutzen der Weblogarbeit als äusserst gering ein. Die Studierenden bei der reflexiven Integration praxisnaher und theoretischer Lernerfahrungen zu unterstützen, ist eine Herausforderung, die dezidierter Anleitung und Förderung durch die Lehrpersonen bedarf
Keywords: Weblog; Blog; e-learning; TEL; higher education; business education

Die Studierenden? - Ein sozio-kultureller Blick auf das Studieren in Bologna-Strukturen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Die hochschulbezogene Lernforschung konzentierte sich bislang vor allem auf das Lernen Studierender im Vorlesungssaal (Classroom Learning). Im Zuge der Bologna-Diskussion stellt sich jedoch vermehrt die Frage, wie Studierende den langfristigen Bildungspfad eines ganzen Studiums gestalten. Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig dazu bekannt, wie Lernaktivitäten ausgewählt und Ressourcen im Studium verteilt werden. Der Beitrag nimmt diese Frage auf und untersucht, welche Handlungsstrategien Studierende bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen entwickeln und welche Rahmenbedingungen dabei eine Rolle spielen.
Keywords: Programmentwicklung; Bologna; Studierende; Kulturpsychologie; Studienprogramm

Studierendenorientierung: Wege und Irrwege eines Begriffs mit vielen Facetten - Reinmann, Gabi; Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Studierendenorientierung ist derzeit eines der Leitkonzepte für die Gestaltung der Lehre an Hochschulen. Ein kritischer Blick offenbart jedoch, dass der Begriff uneinheitlich und mit teils widersprüchlichen Konnotationen gebraucht wird. Der Beitrag analysiert die Begriffsverwendungen innerhalb verschiedener Hochschulkontexte. Dabei werden Widersprüche zwischen den vorgefundenen Konnotationen - insbesondere zwischen den Perspektiven des Hochschulmanagements und der Didaktik - identifiziert. Davon ausgehend wird mit dem Konzept der Bildungsorientierung eine Alternative vorgeschlagen, die auf das Kernziel der Hochschule als Bildungsorganisation verweist und die skizzierten Unschärfen vermeidet.
Keywords: Studierendenorientierung; Hochschulmanagement; Hochschuldidaktik

Developing a learning centered model for designing and managing study programmes - Jenert, Tobias
Research on teaching and learning in higher education has first and foremost centered on individuals, i.e. students' and teachers' approaches to learning and teaching as well as methods (Entwistle, McCune, & Scheja, 2006; Entwistle & Peterson, 2004). As a consequence, concepts on how to improve and innovate education at higher education institutions (HEI) have stayed on the level of individual courses, trying to qualify teachers to implement new teaching and learning methods in their classrooms (Aineley, 2008, S. 619). Yet, there are both theoretical as well as practical reasons that argue for a broader perspective on learning processes and, as a consequence, reach beyond the course-level but focus on entire educational programmes instead: First, over the last thirty years or so, learning theories are increasingly stressing the importance of (a) social-material contexts (McInerney & van Etten, 2002) as well as (b) learners' subjective experiences. This suggests that a course of study be not regarded as a mere addition of more or less independent courses, but rather as a holistic learning experience. This includes the sum total of a student's educationally purposeful social-material interactions at a HEI both within and outside the classroom (cf. Hu & Kuh, 2002). A second, more practical reason why educational researchers and designers should take a closer look on the design of educational programmes lies in the Bologna process: The introduction of the European Credit Transfer System as well as the tow-tiered study structure force HEI to systematically craft their programmes' internal structure. Due to the fact that there are virtually no pedagogical concepts concerning the design of study programmes, these design processes have so far been dominated by administrative considerations, largely neglecting students' experiences within the programme structures (Winter, 2009; Hildbrand, Tremp, Jäger & Tückmantel, 2008). Thus, it can be concluded that there is a lack of knowledge on how distinctive design features of study programmes (1) are perceived by students and (2) impact on their action strategies concerning for example the selection of learning activities, the attribution of resources for learning, and social interactions with their peers.
Keywords: educational development; study programmes; approaches to studying

Learning culture as a prerequisite for an institution-wide approach to educational development - Brahm, Taiga; Gebhardt, Anja; Jenert, Tobias
Over the last two decades, the discussion about innovating teaching and learning at higher education institutions (HEI) has concentrated on various core concepts: such as an increased focus on learning outcomes as competencies and more student-centered teaching. These concepts form part of what Barr and Tagg (1995) have termed the "shift from teaching to learning". However, very few approaches have been proposed so far in the scholarly literature on how to actually transfer such normative concepts into the practice of teaching and learning at HEI. In order to sustainably develop the practices of teaching and learning at HEI, it is necessary to comprehend the prerequisites for educational development. The construct of "learning culture" can be seen as a possible concept to explicate these prerequisites. The aims of this study are to (a) propose an institution-wide approach to educational development at HEI and to (b) present a comprehensive instrument to diagnose learning culture as a starting point for educational development. The findings of the study include a first version of the Learning Culture Inventory for HEI. The students' version of the instrument encompasses 12 scales for the individual, 12 for the pedagogical interactions and 5 for the organizational dimension. The assumed basic factor structure of the instruments could be confirmed. With the institution-wide approach to educational development and the Learning Culture Inventory, this study can provide the basis for sustainable developmental initiatives to innovate teaching and learning at HEI.
Keywords: higher education; instrument development; strategy; educational development

Fertigkeiten und Einstellungen Studierender zum Bloggen in Praxisprojekten oder: Spannungsfelder und Teufelskreise beim selbstorganisierten Lernen - Gebhardt, Anja; Jenert, Tobias
Der Beitrag untersucht die Weblog-Arbeit Studierender zur Dokumentation und Reflexion von Praxisprojekten. Zu Beginn und nach Abschluss einer Lehrveranstaltung mit Praxisphase wurden Studierende zur Weblog-Arbeit befragt. Es zeigt sich, dass die Studierenden kaum über Erfahrungen in der Nutzung von Weblogs verfügen und überwiegend negative Einstellungen zum Bloggen aufweisen. Die Blogeinträge erreichen nicht die angestrebte Reflexionstiefe. Es wird diskutiert, wie das didaktische Design gestaltet werden kann, um die gewünschten Effekte ‒ Peer-Feedback und tiefgehende Reflexion ‒ zu erreichen.
Keywords: Weblog; Selbststudium; Praxisprojekte; Selbstorganisiertes Lernen

Institutionsweite Hochschulentwicklung zur nachhaltigen Gestaltung von Lehr-/Lernkulturen - Jenert, Tobias; Brahm, Taiga

Programmentwicklung zur nachhaltigen Qualitätsentwicklung von Studiengängen - Brahm, Taiga; Jenert, Tobias
Keywords: Hochschulentwicklung

Besseres Feedback, mehr Reflexion? Fertigkeiten und Einstellungen Studierender zum Bloggen in Praxisprojekten - Jenert, Tobias; Gebhardt , Anja (Wissensgemeinschaften. Digitale Medien - Öffnung und Offenheit in Forschung und Lehre)

Konsistente Gestaltung von Selbstlernumgebungen - Jenert, Tobias; Zellweger, Franziska (Kompetenzorientierte Hochschullehre: Die Notwendigkeit von Kohärenz zwischen Lernzielen, Prüfungsformen und Lehr-Lern-Methoden)

Planung und Organisation -Technologieeinsatz von der Bedarfsanalyse bis zur Evaluation - Jenert, Tobias; Brahm, Taiga (Lehrbuch für Lernen und Lehren mit Technologien)

QualiAss - ein Werkzeug zur Prozess- und Qualitätsunterstützung für schriftliche Prüfungen an Hochschulen : Nutzungsszenarien - Spezifikation - Einführung - Jenert, Tobias; Meier, Christoph; Brahm, Taiga (Wissensgemeinschaften: Digitale Medien, Öffnung und Offenheit in Forschung und Lehre)

Vibrational properties of the LiNbO3 z-surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, W. G. (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)
The existence of localized vibrational modes both at the positive and at the negative LiNbO3 (0001) surface is demonstrated by means of first-principles calculations and Raman spectroscopy measurements. First, the phonon modes of the crystal bulk and of the (0001) surface are calculated within the density functional theory. In a second step, the Raman spectra of LiNbO3 bulk and of the two surfaces are measured. The phonon modes localized at the two surfaces are found to be substantially different, and are also found to differ from the bulk modes. The calculated and measured frequencies are in agreement within the error of the method. Raman spectroscopy is shown to be sensitive to differences between bulk and surface and between positive and negative surface. It represents therefore an alternative method to determine the surface polarity, which does not exploit the pyroelectric or piezoelectric properties of the material.

In situ characterization of ZnTe epilayer irradiation via time-resolved and power-density-dependent Raman spectroscopy - Wiedemeier, V; Berth, Gerhard; Zrenner, Artur; Larramendi, E M; Woggon, U; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Laser irradiation damage in ZnTe epilayers was analyzed in situ by power-density-dependent and time-resolved micro-Raman spectroscopy. Damage by ablation or compound decomposition on the sample surface was revealed by the decrease of the ZnTe–nLO mode intensity with the increase of laser power density. The appearance of the peaks associated with the stronger crystalline-tellurium modes, tellurium aggregates and second-order Raman scattering at room temperature μ-Raman spectra was observed for higher power densities than 4.4 × 105 W cm−2. The Raman signal time transients of ZnTe–nLO and crystalline-tellurium modes reveal an exponential evolution of the laser irradiation damage and a fast formation of crystalline tellurium aggregates on the layer surface.

Characterization of SiON integrated waveguides via FTIR and AFM measurements - Frers, Torsten; Hett, Thomas; Hilleringmann, Ulrich; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (2011 Semiconductor Conference Dresden)
Silicon oxynitride (SiON) layers for telecommunication device application are grown by Plasma Enhanced Chemical Vapor Deposition (PECVD) for various gas compositions of SiH4, N2O and NH3. Processing and annealing effects on the oxynitride films were studied by Fourier Transform Infrared Spectroscopy (FTIR) and Atomic Force Microscopy (AFM) measurements. By reduction of the silane (SiH4) gas flow and enhancement of the PECVD deposition temperature, the absorption loss due to NH bands can be nearly completely erased. Furthermore the surface roughness can be reduced by decreasing the gas flow and rising the deposition temperature. First waveguide structures are introduced and their characterization is presented.

Besseres Feedback, mehr Reflexion? – Fertigkeiten und Einstellungen Studierender zum Bloggen in Praxisprojekten - Jenert, Tobias; Gebhardt , Anja (Wissensgemeinschaften : Digitale Medien - Öffnung und Offenheit in Forschung und Lehre)
Der Beitrag untersucht die Weblog-Arbeit Studierender zur Dokumenta¬tion und Reflexion von Praxisprojekten. Zu Beginn und nach Abschluss einer Lehrveranstaltung mit Praxisphase wurden Studierende zum Weblog-Arbeit befragt. Es zeigt sich, dass die Studierenden kaum über Erfahrungen in der Nutzung von Weblogs verfügen und überwiegend negative Einstellungen zum Bloggen aufweisen. Die Blogeinträge erreichen nicht die angestrebte Reflexionstiefe. Es wird diskutiert, wie das didaktische Design gestaltet werden kann, um die gewünschten Effekte - Peer-Feedback und tiefgehende Reflexion - zu erreichen.
Keywords: Weblogs; Selbststudium; Praxisprojekte; Hochschule; Edublog

Short- and long-term impact of remarkable economic events on the growth causes of China–Germany trade in agri-food products - Guo, Zhichao; Feng, Yuanhua; Tan, Xiangyong (Economic Modelling)

A blueprint for event-driven business activity management - Janiesch, Christian; Matzner, Martin; Müller, Oliver (Lecture Notes in Computer Science)
Keywords: Reference architecture; business activity management; business process analytics; business process management; complex event processing

Leaving the Beaten Tracks in Creative Work – A Design Theory for Systems that Support Convergent and Divergent Thinking - Müller-Wienbergen, Felix; Müller, Oliver; Seidel, Stefan; Becker, Jörg (Journal of the Association for Information Systems)
Keywords: Creativity; Creativity Support Systems; convergent thinking; design theory; divergent thinking

Walk your talk: an experimental investigation of the relationship between word of mouth and communicators’ loyalty - Garnefeld, Ina; Helm, Sabrina; Eggert, Andreas (Journal of Service Research)